Managing Water-Related Risks in the West Bengal Sundarbans : Policy Alternatives and Institutions - Sánchez-Triana, Ernesto; Ortolano, Leonard; Paul, Tapas (Taylor and Francis, 2017)
Persistent pressures from water-related threats – sea-level rise, soil and water salinization, and flooding due to embankment overtopping and failure – have made the West Bengal Sundarbans a challenging place to live, and effects of global climate change will only worsen conditions. Four alternative policy directions are examined: business as usual; intensive rural development; short-term out-migration of residents; and embankment realignment and facilitation of voluntary, permanent out-migration. The last of these is the recommended approach. Study findings have informed ongoing deliberations to build consensus on future policy directions for reducing the region’s vulnerability to natural disasters.